Biomass and biowaste new chemical products from old - Balu, Alina M.; Balu, Alina M.; García Nuñez, Araceli; García Nuñez, Araceli (De Gruyter, 2020)
Valorization of biomass focuses on the transformation of biomass molecules into substitutes for petroleum-based chemicals that can be reused. Valorizing Biomass and Biowaste discusses the chemistry and composition of alternative biomass sources. Later chapters will introduce new markets and discuss efficient, green methods of process intensification and catalysis in order to increase conversion of biomass/biowastes